2005
DOI: 10.1097/01.ta.0000179952.95921.49
|View full text |Cite
|
Sign up to set email alerts
|

Prone Positioning Improves Oxygenation in Post-Traumatic Lung Injury—A Prospective Randomized Trial

Abstract: Intermittent prone positioning was not able to reduce the duration of mechanical ventilation in this limited number of patients. However the oxygenation improved significantly over the first four days of treatment, and the prevalence of ARDS and pneumonia were reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
128
0
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(135 citation statements)
references
References 33 publications
0
128
0
7
Order By: Relevance
“…40 For the primary outcome, there was no loss to follow-up in 4 trials. 17,35,37,38 In the remaining 6 trials, less than 5% of patients were lost to follow-up (12/802, 16 6/142, 36 (range 4%-32% of all patients), which involved 0%-41% of patients initially assigned to prone positioning and 0%-21% of those assigned to the supine group.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…40 For the primary outcome, there was no loss to follow-up in 4 trials. 17,35,37,38 In the remaining 6 trials, less than 5% of patients were lost to follow-up (12/802, 16 6/142, 36 (range 4%-32% of all patients), which involved 0%-41% of patients initially assigned to prone positioning and 0%-21% of those assigned to the supine group.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…All of the RCTs analyzed outcomes by assigned group. Seven studies were ended early because of slow recruitment 15,[34][35][36]38,39 or on the basis of a stopping rule for futility. 37 One trial at high risk of bias did not report mortality.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…A meta-analysis of 7 studies involving prone positioning was reported in 2011 by Abroug et al 81 Three earlier studies included a mix of ALI and ARDS patients, applied the prone position for a shorter duration (7-11 h/d), and did not apply LPV. [82][83][84] The 4 later studies included only patients with ARDS, applied the prone position longer (17-24 h/d), and applied an LPV strategy in all patients. [85][86][87][88] Overall ICU mortality for the entire group was not reduced with prone position, but there was a significant improvement when the later 4 studies were analyzed separately.…”
Section: Acute Lung Injury and Acute Respiratory Distress Syndromementioning
confidence: 99%